PERBANDINGAN KUALITAS PELAYANAN KELUARGA BERENCANA (KB) ANTARA BIDAN PRAKTIK SWASTA (BPS) DENGAN PUSKESMAS DI KABUPATEN SLEMAN - YULIANTI, ERMA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Results of data Indonesian Demographic and Health Survey (IDHS) in 2007 and 2012 recorded an increase in users of family planning services in private care resources as much as 69 percent to 73 percent, between the source of the private family planning services, Private Practice Midwife (CPM) was recorded as a source of service the most widely accessible to the public by 32 percent. Conditions increased users of family planning services in private care resources also occur in Special Region of Yogyakarta (DIY), with most users of family planning services in Private Practice Midwife. This thesis aims to compare the quality of family planning services among Private Practice Midwife with community health centers in Sleman and to identify why users choose Private Practice Midwife (CPM) in making family planning services. This study used a qualitative approach. Primary data were collected through observation of the implementation of family planning services and indepth interviews of the informant (Puskesmas, Private Practice Midwife, Field Officer KB, users, etc). Secondary data were obtained from reports achievement of family planning services, health center reports, and other documentation sources. From the results: first, the quality of family planning services in the private midwives tend to be better than the family planning services in health centers, especially in the aspect of interpersonal relationships between staff and users of private midwife, the assessment is more friendly, schedule a private provider of family planning services in a more flexible limited compared to the health center only 1 to 3 times a week, the time of service at a private provider that is longer than the limited health center only half a day, waiting times service at a private provider faster rather than in health centers, and service procedures are simple in private midwife compared to the procedures in health centers is quite complicated perceived by users. Secondly, the reason users prefer family planning services in the schedule caused private midwives services in a more flexible, affordable place closer CPM services in the community, the number of resources for family planning services (private midwife) more and spreading in the community, interpersonal relationships between officers and users of family planning services are considered more friendly, more simple service procedures, and the choice and availability of contraceptive methods is more complete with the brand and quality selection more diverse. These factors are also included in the assessment variable quality of family planning services, so it can be concluded reasons for selecting users to access source of family planning services in Private Practice Midwife is because family planning services in CPM better quality.